Ταξίδι στα Κύθηρα - Μονάδα εναλλακτικού τουρισμού στην Παλαιόχωρα Κυθήρων - Βερδούκα, Μαρία (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Αρχιτεκτόνων Μηχανικών, 2015)
The project deals with the design of a retreat nestled within a landscape environment and the study of the approach towards it, and the study of imagery and experience that can be created within a landscape. The design approach centres on concepts of the framing of the eye’s view, vistas and movement and their inherent narrative qualities, and their use as synthetic design tools, as well as light and colour of the landscape environment as elements of space. It also attempts to use other narrative concepts in the development of form and function, such as symbolism and reference, exploring examples of architectural heritage and language.